IMPACT OF ONLINE WORKING MODE ON THE WORK LIFE BALANCE (WLB): AN EMPIRICAL ANALYSIS OF BANKING SECTOR EMPLOYEES IN DELHI-NCR, INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This study examines the impact of telecommuting  on work-life balance among bank employees  in Delhi NCR. So, we chose 100 employees  from banks like SBI and ICICI to write this  paper. However, the online working mode  changed their accountability, duties, tasks, and  responsibilities at home and work. Moreover,  the data were collected from a variety of sources  and were collected while working online. It was  collected via postal questionnaire and telephone  interview using simple random sampling to  ensure that all banking sectors were represented.  Using ANOVA, we compared the difficulty of  achieving work-life balance (WLB) in public  and private sector banks. ANOVA was used  to analyses the data, but also percentage and  mean score. The ANOVA result shows that  the obtained value is higher than the table  value, rejecting the null hypothesis. It means  that achieving WLB at different hierarchies is  significantly more difficult. The study found that  employees in the banking sector had increased  workloads when working online. WLB is  difficult to achieve when working online.
Keywords: Work-Life Balance; online working mode; Banking Sector; ANOVA; Empirical analysis